Modified Algar–Flynn–Oyamada Reaction for the Synthesis of 3-Hydroxy-2-styryl-chromen-4-ones under Solvent-Free Conditions - Dinesh Kumar (Chemistry Proceedings, 2022)
The simple and efficient conditions for a Algar–Flynn–Oyamada reaction for the synthesis of 3-hydroxy-2-styryl-chromen-4-ones involving the grinding of different 1-(2′-hydroxy-phenyl)-5-aryl-penta-2,4-dien-1-ones with UHP (urea–hydrogen peroxide), pulverized potassium hydroxide and a few drops of ethanol at room temperature under solvent-free conditions are described. A presented protocol offers a faster reaction and a higher yield compared to conventional methods. The structure of the synthesized compounds was identified from their spectral data (IR, 1H-NMR).